Analisis Potensi Daya Tarik Air Terjun Tembok Barak Untuk Dikembangkan Menjadi Destinasi Wisata Desa Sambangan - I Gusti Ayu Ketut Asti Wedayanti; Risa Panti Ariani; Made Riki Ponga Kusyanda (Universitas Pendidikan Ganesha, 2023)
This study aims to describe the potential attractiveness of Tembok Barak Waterfall which can be developed as a tourist destination in Sambangan Village. The type of research used is descriptive qualitative. The research subjects were determined using a purposive sampling technique, namely key informants: Chairperson of the Tunjung Mekar POKDARWIS, Head of the Tembok Barak Waterfall Group and supporting informants: Community Leaders, Tour Guides (Guide), and Tourism Sector Staff of the Buleleng Regency Tourism Office. The method used in this study is the method of observation, interviews, documentation. The results showed that the potential attractiveness of the Barak Wall Waterfall included: attractions (tourist attractions) in the form of natural conditions that are owned and there are springs that are used by the surrounding community for painting activities. Accessibility (accessibility) in the form of adequate road access for tourist activities which also serve as trekking routes and views of rice fields on the entry route. In the amenities component, there is a resting place in the form of a saka pat (a simple open building with four pillars) and there are food and beverage services in the form of a simple local shop. Ancillary (additional services) at Tembok Barak Waterfall, namely the establishment of a Tourism Management Body called the Tunjung Mekar Tourism Awareness Group (POKDARWIS) and have received training from academia and the Tourism Office related to managers. Based on the results of the research above, it can be concluded that Tembok Barak Waterfall has the potential to be developed into a natural tourist destination in Sambangan Village.